I scream for ice cream ebook I can read level 1. - Scotton, Rob (I Can Read, Level 1: Splat the Cat., 2015)
Join Splat and his class on a field trip to an ice-cream factory in this delectable I Can Read book from New York Times bestselling author-artist Rob Scotton. Splat can barely sit still during the bus ride. He's imagining the mountain of ice cream he thinks he'll get to eat! But when Splat gets there, that mountain becomes more of an avalanche. It's up to Splat and his classmates to save the day! Beginning readers will practice the –eam sound in this easy-to-read addition to the Splat series. Splat the Cat: I Scream for Ice Cream is a Level One I Can Read book, which means it's perfect for children learning to sound out words and sentences. Whether shared at home or in a classroom, the short sentences, familiar words, and simple concepts of Level One books support success for children eager to start reading on their own.